THE EFFECT OF HUMAN RESOURCE QUALITY AND COMPANY SIZE ON THE PREPARATION OF FINANCIAL REPORTS BASED ON EMKM SAK IN PALOPO CITY, MODERATED BY CAPITAL LEVEL - Chairulnisa, Nisa; Nurun Nuraini; Nurfadilah; Muhammad Ikram (International Journal of Multidisciplinary Reseach, 2026)
This study discusses the level of financial reporting based on SAK EMKM (Financial Accounting Standards for Micro, Small and Medium Entities) focusing on the city of Palopo, through an analysis of human resource quality (HR) factors and company size with company size as a strengthening factor between the two. This study aims to analyze the influence of human resource quality and company size on the preparation of financial reports based on SAK EMKM (Financial Accounting Standards for Micro, Small and Medium Entities) among MSMEs in the city of Palopo, with the level of capital as a moderating variable. The type of research used in this study is a quantitative method, data collected through questionnaires and interviews with MSME owners who already have a Brand in the city of Palopo. After that, the data was analyzed using the SEM method supported by the SPSS application to determine the variables that significantly influence the recording of financial reports based on SAK EMKM. The results of the study indicate that the quality of human resources has a significant effect on the preparation of financial reports based on SAK EMKM. While company size does not affect the recording of financial reports based on SAK EMKM. In addition, this study also found that the level of capital does not moderate the relationship between the quality of human resources and company size on the recording of financial reports based on SAK EMKM in Palopo City.